Effect of Excessive Fe2O3 on Microstructural Evolution of Micro/Nanocrystalline 2205 Duplex Stainless Steel Prepared by Aluminothermic Reaction - Zheng, Yuehong; Zhao, He; Zhang, Na; La, Peiqing; Shi, Yu; Zhu, Min; Zhan, Faqi (Frontiers in Materials, 2020)
It is one of the effective ways to obtain excellent comprehensive performance of 2205 duplex stainless steel (DSS) to adjust the volume ratio and grain size of α and γ phases. In present paper, 2205 DSSs with micro-nano structures were successfully prepared by aluminothermic reaction under appropriate Fe2O3 excess conditions, and the formation mechanism of micro/nano structures was studied from the aspects of the preparation process, element equivalent and residual Al content. Here, the Creq/Nieq ratio of the 2205 DSS is 2.09, indicating that the solidification mode belongs to mode F, that is: L → L + α → α → α + γ. The residual Al content, the volume percentages of α and γ phases and their grain sizes can be controlled by reasonably adjusting the excess percentage of Fe2O3. When the excess percentage of Fe2O3 is 5.0%, the volume percentages of α and γ phases reach the minimum and maximum values, respectively. However, when there is a large amount of unreacted Al in the alloy or an inappropriate excess percentage of Fe2O3 for preparation, only the α phase is contained in alloys.